Managing Disintegration: How the European Parliament Responded and Adapted to Brexit - Bressanelli, Edoardo (2021)
Brexit makes both a direct and an indirect impact on the European Parliament (EP). The most direct consequence is the withdrawal of the 73-member strong UK contingent and the changing size of the political groups. Yet, the impact of Brexit is also felt in more oblique ways. Focussing on the role and influence of the EP in the EU–UK negotiations, and of the British delegation in the EP, this article shows that the process, and not just the outcome of Brexit, has significant organisational implications for the EP and its political groups. Moreover, it also showcases the importance of informal rules and norms of behaviour, which were affected by Brexit well ahead of any formal change to the UK status as a Member State. The EP and its leadership ensured the active involvement of the EP in the negotiating process—albeit in different ways for the withdrawal agreement and the future relationship—and sought to minimise the costs of Brexit, reducing the clout of British members particularly in the allocation of legislative reports.